Capturing Killer Acquisitions in Digital Markets under the European Union Merger Control Rules (TEST Trento Student Law Review, 2023)
A few years ago, a novel development identified as "Killer Acqui- sitions" surfaced within the domain of EU Merger Control: incumbent undertakings were under suspicion of acquiring promising startups with the intent of eliminating prospective market competitors. Big Tech companies in digital markets are among the usual suspects in this kind of transaction. While this strategy can surely serve to cement incumbent platforms' dominant position in the digital markets, the issue resides in the impracticability of capturing these acquisitions within the framework of EU Merger Control regulations due to the impossibility of complying with the stipulated threshold requirements which respectively brought about the enhancement of the European Commission's toolbox. This paper will display the options to carry out those amendments and what options were opted for. It will address whether the proposed methodo- logies for addressing killer acquisitions represent viable solutions to the issue. This paper aims to clarify the challenges faced by digital platforms engaged in business operations and strategic merger and acquisition plan- ning within the European Union. This work's focus is also on elucidating the challenges that digital platforms engaged in business operations and mergers and acquisitions within the EU may confront.
Keywords: Killer Acquisition; EU Merger Control; Article 22 Referrals; EUMR; DMA; Article 102 TFUE